ANALISIS PENGARUH SERVICESCAPE TERHADAP KEPUTUSAN PEMBELIAN DI KITCHEN YARD RESTO HOTEL MERCURE TANGERANG BSD CITY - Maria Vermilia Berinthia; Roels Ni Made Sri Puspadewi (Cross-border, 2023)
This study aims to determine whether servicescape has an influence on consumers purchase decision at Kitchen Yard Mercure Hotel Tangerang, BSD City. The researcher was conducted this research by using descriptive quantitative research methods. Data obtained from the results of distributing questionnaires conducted online by using google form to 100 respondents. The questionnaire consisted of 28 statements with a Likert scale type. The results of the questionnaire were processed using a tool in the form of SPSS version 25. The results of this research are the majority of woman aged 18 – 24 years. Based on the validity and reliability test of all the statements are valid and reliable. Servicescape can explain 70,5% of the Purchase Decision variables, while other 29,5% are influenced by other variables not explained in this study. Based on a simple linear regression test, the regression coefficient X shows the number 1,260 therefore every 1% addition to servicescape, the purchase decision will increase 1,260. The results of the T test, it can be seen that the variable of servicescape have a positive and significant effect on purchase decision. Based on the results of this study, suggestions for Kitchen Yard Mercure Hotel Tangerang, BSD City is that it can expand the arrangement of existing restaurant facilities to improve the convenience of consumers in making purchases and in their interactions with employees.